PDGFR‐β‐activated ACK1‐AKT Signaling Promotes Glioma Tumorigenesis. Issue 8 (8th October 2014) - Zhang, Jiannan; Chen, Tao; Mao, Qin; Lin, Jinbo; Jia, Jun; Li, Shanquan; Xiong, Wenhao; Lin, Yingying; Liu, Zhiqiang; Liu, Xiaoyu; Zhao, Hailiang; Wang, Guisong; et al.
<x xml:space="preserve">Abstract</x> Aberrant PDGF‐PDGFR signaling and its effects on downstream effectors have been implicated in glioma development. A crucial AKT regulator, ACK1 (TNK2) has been shown to be a downstream mediator of PDGF signaling; however, the exact underlying mechanisms in gliomas remain elusive. Here, we report that in glioma cells, PDGFR‐β activation enhanced the interaction between ACK1 and AKT, resulting in AKT activation. PDGF treatment consistently promoted the formation of complexes containing PDGFR‐β and ACK1. Mutational analysis suggested that Y635 of ACK1 is a PDGFR‐β phosphorylation site and that the ACK1 Y635F mutant abrogated the sequential activation of AKT. Moreover, PDK1 interacted with ACK1 during PDGF stimulation, which is required for the binding of ACK1 to PDGFR‐β. Further mutational analysis showed that T325 of ACK1 was crucial for the ACK1 and PDK1 interaction. ACK1 Y635F or T325A mutants abolished PDGFR‐β‐induced AKT activation, the subsequent nuclear translocation of β‐catenin and the expression of cyclin D1. Glioma cell cycle progression, proliferation and tumorigenesis were accordingly blocked by ACK1 Y635F or T325A. In glioblastoma multiforme samples from 51 patients, increased ACK1 tyrosine phosphorylation correlated with upregulated PDGFR‐β activity and AKT activation. Taken together, our data demonstrate that ACK1 plays a pivotal role in PDGF‐PDGFR‐induced AKT signaling in glioma tumorigenesis. This knowledge contributes to our understanding of glioma progression and may facilitate the identification of novel therapeutic targets for future glioma treatment.